1989
DOI: 10.1210/jcem-68-3-572
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Growth Hormone (GH)-Secreting Adenomatous Human Pituitaries Release Somatostatin and GH-Releasing Hormone

Abstract: Neuropeptides such as vasoactive intestinal peptide, LHRH, or TRH have been found in rat pituitary tissue and could act via paracrine or autocrine actions in this tissue. In this study we investigated whether normal human pituitary tissue and GH-secreting human pituitary adenomas could release somatostatin (SRIH) and GHRH. Fragments from three human pituitaries and dispersed cells from six GH-secreting adenomas (four adenomas were studied for GHRH release and five for SRIH release) were perifused using a Krebs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

1992
1992
1999
1999

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 6 publications
2
25
0
2
Order By: Relevance
“…Several clinical observations have suggested that GH pulses in this disease are generated probably within the tumor, rather than from physiological input signals such as growth hormone-releasing hormone (GHRH) and somatostatin (1,3,4,19). Further evidence for the tumoral origin of pulses was obtained by others in in vitro data of adenoma tissue, which exhibits episodic GH release in the absence of hypothalamic GHRH and somatostatin (20,21). The presence of a pituitary tumor per se does not decrease the regularity of GH secretion, since we have observed normal ApEn values for plasma GH profiles in five patients with untreated prolactinomas (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Several clinical observations have suggested that GH pulses in this disease are generated probably within the tumor, rather than from physiological input signals such as growth hormone-releasing hormone (GHRH) and somatostatin (1,3,4,19). Further evidence for the tumoral origin of pulses was obtained by others in in vitro data of adenoma tissue, which exhibits episodic GH release in the absence of hypothalamic GHRH and somatostatin (20,21). The presence of a pituitary tumor per se does not decrease the regularity of GH secretion, since we have observed normal ApEn values for plasma GH profiles in five patients with untreated prolactinomas (unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that GHRH may, in consort with the competing hypophysiotropic hormone somatostatin, exert some degree of local neuroendocrine control over normal pituitary function. 48,52 In calling attention to a possible role for locally generated hypothalamic hormones in the progression of somatotroph adenomas, these data provide the basis of a new paradigm from which to view the biology and pathogenesis of these neoplasms. Historically, the development and progression of pituitary tumors have been the subject of two conceptually opposing theories.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin and GHRH secretion occur, both in GH-secreting adenoma cells and in normal human pituitary cells. TRH stimulates somatostatin release from normal cells, while inhibition of somatostatin has been demonstrated after TRH in adenomatous tissue (36). These findings may be of interest in relation to paradoxical GH responses.…”
Section: Journal Of Endocrinology (1999) 140mentioning
confidence: 68%